Analisis Lagu “Bulan Dikekang Malam” Dari Rossa Menggunakan Pendekatan Objektif - Mastura, Leni (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
The song is a part of musical art that combines lyrical texts with melody and rhythm. Song lyrics are expressions of thoughts and feelings, crafted into messages or meanings the musician intends to convey. One song that holds deep meaning is